Magneto-induced Mullins effect of anisotropic MREs under compression mode. (22nd January 2021) - Gan, Ruyi; Qi, Song; Zhao, Yi; Fu, Jie; Li, Shixu; Li, Yaping; Yu, Miao
Abstract: The filled elastomer materials exhibit obvious stress-softening phenomenon after initial stretching, which is called the Mullins effect. Since magnetorheological elastomers tend to work under a magnetic field, it will show a different magneto-induced Mullins effect of traditional materials. Therefore, in this paper, the effects of anisotropy, magnetic flux density, pre-strain and compression times on the magneto-induced Mullins effect were studied by rheometer. The results demonstrated that, under a fixed magnetic flux density, when the arrangement of magnetic particles is perpendicular to the magnetic field, the residual strain energy of the material is the smallest. This indicates that the magneto-induced Mullins effect is the weakest and the stability of the material is the best. Meanwhile, when the compression pre-strain is constant, the materials will show an obvious stress-hardening phenomenon under magnetic field. When the arrangement of magnetic particles is 30° to the magnetic field, the force between the particles is the smallest. This indicates that the magneto-induced Mullins effect is the weakest and the performance stability is the best. At the same time, this paper attempts to establish the corresponding model of the magneto-induced Mullins effect from the perspective of strain energy. The error between the fitting and the experimental results is less than 3%, which shows that the model can well explain the phenomena obtained in the experiment.